A Building Information Modelling (BIM) Approach to the Systematic Management of Construction Projects. Issue 1 (June 2021) - Ershadi, Mahmoud; Jefferies, Marcus; Davis, Peter; Mojtahedi, Mohammad
Abstract: Recent advancements in information technology have benefited the construction sector in more effective storage, analysis, and transmission of information. Making proper project decisions is hinged upon the verified and timely information provided by systems. It is especially the case in large construction projects in which many partners collaborate to deliver a project. Building information modeling (BIM) as an intelligent 3D model-based approach provides construction managers with insight on how to integrate elements of project configuration. In this paper, we theorize the potential contribution of BIM to the systematic management of projects at the project and corporate level. The findings guide practitioners on how to take advantage of this approach towards the integrated planning and control of construction projects.